The Awareness of the Jordanian Population Regarding Intranasal Corticosteroids' Uses for Allergic Rhinitis - Al-Balas, Hasan Ibrahim; Khamees, Almu'atasim; Okour, Tala Abd Aljaleel; Ababneh, Ruaa Ismail; Al-Smadi, Bara' Hussein; Almomani, Leen Mohamad; BaniHani, Reem Nazem; AlRawashdeh, Marah Akram (International Archives of Otorhinolaryngology, 2025)
Intranasal corticosteroids are widely regarded as the most efficacious remedy for managing moderate to severe allergic rhinitis. However, the Jordanian population's understanding and attitudes toward the safe and proper use of these medications remain ambiguous.This study was undertaken to evaluate Jordanian individuals' awareness of intranasal corticosteroids by examining their present perceptions, attitudes, and behaviors regarding these pharmaceuticals.We conducted a cross-sectional study within the adult Jordanian demographic using an online survey based on a structured questionnaire.The study comprised 1509 participants, revealing that 34.2% of the adult Jordanian population suffers from allergic rhinitis, with a prevalence of 39.5% in males and 60.5% in females. Among individuals with allergic rhinitis, 34.1%, 38.4%, 67.1%, and 43.2% hold beliefs regarding the impact of intranasal corticosteroids on blood sugar, blood pressure, pregnancy, and obesity, respectively. Notably, 67.8% of allergic rhinitis patients in our study actively use intranasal corticosteroids, and users demonstrate a significantly higher level of awareness compared with non-users, as we found significantly higher awareness levels among allergic rhinitis patients regarding possible side effects compared with non-allergic rhinitis group (p-value = < .0001, 0.0019, 0.0109, <.0001 and 0.0034) for blood sugar, blood pressure, pregnancy, children less than 5 years and obesity respectively.The results obtained from this research underscore the critical need for educational initiatives and interventions to enhance understanding and utilization of these medications within Jordan. These efforts can significantly contribute to improved patient outcomes and decreased healthcare expenses.
Keywords: allergic rhinitis; intranasal corticosteroids; awareness; knowledge